The Patient Population at Homeopathic Outpatient Clinics across India: A Clinical Data Collection Study - Kaur, Harleen; Jain, Surbhi; Katarmal, Daisy; Sachdeva, Jyoti; Ponnam, Hima Bindu; Muraleedharan, K. C.; Parveen, Suraia; Raizada, Sonia; Karso, Liyi; Bala, Renu; Srivastava, Amit; Shinde, Vaishali; Ramteke, Sunil; Choubey, Gurudev; Kundu, Chittaranjan; Ramanan, Vinitha E.; Patole, Tejaswini; Sonny, Ranjit; Bhattacharjee, Baidurjya; Sardarla, Ravi Kumar; Bawaskar, Ramesh S.; Reddy, G. R. C.; Avinash, Kumar Keshav; Tamang, Santosh; Prusty, Akhyaya Kumar; Sadhukhan, Madhumita; Maglara, Artemis; Garoufali, Anastasia; Stassinopoulos, Michael; Lilas, Theodoros; Tapakis, Lefteris; Khurana, Anil; Manchanda, Raj K. (Homeopathy, 2024)
Background Even though several initiatives have been undertaken in different locations worldwide to collect clinical data in homeopathy, it is important to further investigate these aspects in the context of health care in India.Objective The study aimed to gather and analyze patients' clinical data and to derive insights into homeopathic treatment using an internet-based software program for data storage, retrieval and repertorization.Methods A multi-center observational study was conducted across 14 homeopathy outpatient clinics in India that are affiliated with the Central Council for Research in Homoeopathy (CCRH). Patient symptoms and demographic details were documented anonymously, and prescriptions were guided by repertorial suggestions from the Vithoulkas Compass software. During follow-up visits, treatment outcome was also recorded using an online assessment form. A retrospective analysis of data on patients' demographics, follow-up visits, morbidity (International Classification of Diseases 11th Revision), rubrics used, prescribed medicines and the level of improvement was achieved using Microsoft Excel-generated pivot tables.Results Throughout the study duration of one year a total of 2,811 patients attended the 14 outpatient clinics, of whom 2,468 were new patients with a total of 2,172 initial homeopathic prescription entries. Across the study, there were 3,491 prescriptions and 1,628 follow-up consultations for 868 follow-up patients, all of which data were thoroughly analyzed. The highest frequency of patients was in the 20–49 age group, and a higher proportion of the patients overall was female. Musculoskeletal, dermatological and respiratory complaints were the most frequently reported. The rubrics “Desire for sweets” and “Desire for spices” emerged as the most commonly used in the repertorizations. Further, Sulphur stood out as the most commonly prescribed medicine overall. With homeopathic treatment, some degree of clinical improvement was reported in 86% of the follow-up cases.Conclusion Homeopathy is prescribed in CCRH outpatient clinics for a wide range of ailments in people across India, with at least some clinical improvement noted in a high proportion of those patients. The large-scale systematic data collection in these clinics has provided clear insights into the use and clinical value of homeopathy in India, with the potential to build a substantive nationwide data inventory over time.
Keywords: homeopathy; data collection; clinical data; rubrics; India